GABAA Receptor Subunit Composition Drives Its Sensitivity to the Insecticide Fipronil - Soualah, Zineb; Taly, Antoine; Crespin, Lucille; Saulais, Ophélie; Henrion, Daniel; Legendre, Claire; Tricoire-Leignel, Hélène; Legros, Christian; Mattei, César (Frontiers in Neuroscience, 2021)
Fipronil (FPN) is a worldwide-used neurotoxic insecticide, targeting, and blocking GABAA receptors (GABAARs). Beyond its efficiency on insect GABAARs, FPN causes neurotoxic effects in humans and mammals. Here, we investigated the mode of action of FPN on mammalian α6-containing GABAARs to understand its inhibitory effects on GABA-induced currents, as a function of the synaptic or extrasynaptic localization of GABAARs. We characterized the effects of FPN by electrophysiology using Xenopus oocytes which were microtransplanted with cerebellum membranes or injected with α6β3, α6β3γ2S (synaptic), and α6β3δ (extrasynaptic) cDNAs. At micromolar concentrations, FPN dose-dependently inhibited cerebellar GABA currents. FPN acts as a non-competitive antagonist on ternary receptors. Surprisingly, the inhibition of GABA-induced currents was partial for extra-synaptic (α6β3δ) and binary (α6β3) receptors, while synaptic α6β3γ2S receptors were fully blocked, indicating that the complementary γ or δ subunit participates in FPN-GABAAR interaction. FPN unexpectedly behaved as a positive modulator on β3 homopentamers. These data show that FPN action is driven by the subunit composition of GABAARs – highlighting the role of the complementary subunit – and thus their localization within a physiological synapse. We built a docking model of FPN on GABAARs, which reveals two putative binding sites. This is consistent with a double binding mode of FPN on GABAARs, possibly one being of high affinity and the other of low affinity. Physiologically, the γ/δ subunit incorporation drives its inhibitory level and has important significance for its toxicity on the mammalian nervous system, especially in acute exposure.